(untitled) (Bangladesh Journal of Medicine, 2024)
Background: Although there are several antivirals available against hepatitis-B, they have several limitations including infinite duration of administration, viral resistance, adverse events and failure of prevention of liver disease progression in all cases. Therefore the quest for a new antiviral against heptatitis-B continues. Methods: Phase-1, 2 & 3 clinical trials of a novel therapeutic vaccine for hepatitis-B called NASVAC were conducted in treatment naive chronic hepatitis-B patients in Bangladesh. Subsequently the patients were followed up off treatment for upto 3 years. Results: Results show that NASVAC treated patients achieved better virologic control compared to those treated with pegylatedinterferon. NASVAC was not only found to be safe, it also induced immune modulation and most importantly unlike those patients who were treated with pegylatedinterferon, there was no progression of liver disease in NASVAC treated patients. NASVAC has subsequently been registered in five different countries and its recipe has been approved by the Drug Control Committee of Bangladesh Government. Conclusion: NASVAC appears to be an effective therapeutic agent for chronic hepatitis-B, free from adverse events and of finite duration that prevents liver disease progression. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 155